Combination of anti-early apoptotic cell autoantibodies and anti-SSA autoantibodies in lupus nephritis - Aktar, Kamal; Liu, Xiang; Yang, Xiaowei (Cellular and Molecular Biology, 2018)
The aim of this study was to investigate the association of anti-early apoptotic cell autoantibodies, anti-SSA, and anti-SSB with clinical features of lupus nephritis (LN). Multiparameter flow cytometry was used to determine early apoptotic cells and for measuring the simultaneous binding of annexin V, 7-AAD, and IgG from LN patients (n = 39). The association between clinical features of LN and autoantibodies against early apoptotic cells, and between the autoantibodies and anti-SSA and anti-SSB, were further investigated. Thirteen LN patients (33.3 %) were positive for autoantibodies against early apoptotic cells. The prevalence of anti-SSA and anti-SSB were similar in patients with anti-early apoptotic cell autoantibodies and those without (anti-SSA: 9/13 versus 15/26; anti-SSB: 3/13 versus 4/26). Anti-early apoptotic cell antibody-positive patients had lower C3 levels (0.34 ± 0.22) than the antibody-negative patients (0.47 ± 0.17, p = 0.059); and significantly higher anti-dsDNA levels (502.99 ± 275.48 versus 214.13 ± 229.29, p = 0.001). In univariate logistic regression analysis, the presence of anti-early apoptotic cell antibody could predict poor short-term prognosis (HR 7.500, 95 % CI: 1.210 - 46.504, p = 0.030), while patients who were double positive for anti-SSA and anti-early apoptotic cell antibody had significantly increased risk of poor short-term outcome (HR 17.500, 95 % CI: 2.500 - 122.500, p = 0.004). The combination of anti-early apoptotic cell autoantibodies and anti-SSA might be of predictive value in LN.